2009
DOI: 10.1016/j.jsams.2008.12.628
|View full text |Cite
|
Sign up to set email alerts
|

Raising the standards of the calf-raise test: A systematic review

Abstract: The calf-raise test is used by clinicians and researchers in sports medicine to assess properties of the calf muscle-tendon unit. The test generally involves repetitive concentric-eccentric muscle action of the plantar-flexors in unipedal stance and is quantified by the number of raises performed. Although the calf-raise test appears to have acceptable reliability and face validity, and is commonly used for medical assessment and rehabilitation of injuries, no universally acceptable test parameters have been p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 62 publications
2
76
0
3
Order By: Relevance
“…6,16,28 Many studies have used the reduction in heel raise height as an indicator of triceps surae muscle fatigue and a termination criterion for the heel raise test, and, recently, as a measure of decreased triceps surae muscle-tendon unit function. 20,45 The confirmatory GEE analysis supports these practices, estimating a 13.3-mm drop in heel raise height from the early to the late phase (P<.001), which demonstrates a decline in heel raise test performance. 35 This is the first study to provide an estimate of the amount of variation in heel raise height during 2 heel raise test versions when individuals are instructed to attempt maximum heel raise height during each raise and the test is not terminated if a certain height is not reached.…”
Section: Extent Of Knee Angle Variabilitymentioning
confidence: 67%
See 2 more Smart Citations
“…6,16,28 Many studies have used the reduction in heel raise height as an indicator of triceps surae muscle fatigue and a termination criterion for the heel raise test, and, recently, as a measure of decreased triceps surae muscle-tendon unit function. 20,45 The confirmatory GEE analysis supports these practices, estimating a 13.3-mm drop in heel raise height from the early to the late phase (P<.001), which demonstrates a decline in heel raise test performance. 35 This is the first study to provide an estimate of the amount of variation in heel raise height during 2 heel raise test versions when individuals are instructed to attempt maximum heel raise height during each raise and the test is not terminated if a certain height is not reached.…”
Section: Extent Of Knee Angle Variabilitymentioning
confidence: 67%
“…doi:10.2519/jospt.2011 [ research report ] tendon unit, the heel raise test most commonly involves performing unilateral heel raises until fatigue. 20 Fatigue during the heel raise test has been defined as the inability to continue performing a "proper" heel raise, 35 where a decrease in performance can be observed by a reduction in heel raise height or pace, loss of balance or forward lean, or inability to maintain a defined knee position. 21 The total number of heel raise repetitions completed to this point is counted and used as the main clinical outcome measure.…”
Section: T T Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…One complete heel raise was defined by 2 consecutive heel-to-floor contacts and included a data point when the heel was at maximal height during that raise as identified in Figure 1. The chosen heel-raise parameters for balance support, body position, and pace were based on those most frequently cited in the literature (15) and used in a previous study (17). An overview of subjects' position and apparatus used for heelraise testing is provided in Figure 2.…”
mentioning
confidence: 99%
“…[4,5] In a systematic review done by Kim Hébert-Losiera et al on parameters of Calf raise test, it was found that most studies gave an average value of 27 repetitions in healthy adults and 19 repetitions in pathological subjects. [12] However, this normative grading method does not take into consideration the age of the subject. There is a possibility that the normative values may not be same for all the ages owing to degenerative changes in the muscle tissue and reduced function in normal subjects as well.…”
Section: Introductionmentioning
confidence: 99%